2021
DOI: 10.24996/ijs.2021.62.11(si).15
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of P3HT: ZnO Solar Cells by Incorporating Metal Oxide Fe2O3 Nanoparticles

Abstract: The ferric oxide nanoparticles (Fe2O3) which are deposited at interface which is related to hole collecting buffer layer [poly(3,4-ethyl-enedioxythiophene): poly(styrene-sulfonate) (PEDOT: PSS)] as well as regioregular poly(3-hexyl-thiophene): Zinc oxide nanoparticles (P3HT): (ZnO) active layer have been considerable increasing the performance of solar cell. Also, the solar cell devices have been fabricated with a weight ratio of 1:0.7, 1:0.8, 1:0.9 and 1:1 of P3HT and ZnO, respectively. In addition, photo phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…22 Some reports also indicated that iron oxides also could be used to boost the efficiency of polymer solar cells. 79…”
Section: Dye-sanitized Solar Cells (Dsscs)mentioning
confidence: 99%
See 3 more Smart Citations
“…22 Some reports also indicated that iron oxides also could be used to boost the efficiency of polymer solar cells. 79…”
Section: Dye-sanitized Solar Cells (Dsscs)mentioning
confidence: 99%
“…It was found that the optimized polymer solar cell with a PEDOT:PSS:Fe 2 O 3 layer had a short circuit current of 10.91 mAcm −2 , V OC of 0.92 V, FF of 0.42, and PCE of 4.1%. 79 Other reports on using iron oxides as a photoactive part in solar cell devices are tabulated in Table 1.…”
Section: Iron Oxides As the Primary Part Of Solar Cell Devicesmentioning
confidence: 99%
See 2 more Smart Citations